Morphometric analysis of the skull of Hamdani sheep via Three-Dimensional modelling - Dayan, Mustafa Orhun; Demircioglu, Ismail; Kocyigit, Ali; Guzel, Baris Can; Karaavci, Funda Aksunger (Wiley, 2023)
The aim of the present study was to determine the craniometric characteristics of the crania of Hamdani sheep, one of local breeds of Turkey, by using computed tomography (CT). In the study, 13 (six female and seven male) skulls were used. After CT images of the skulls were taken, their three-dimensional models were created by MIMICS 20.1 (The Materialise Group, Leuven, Belgium) program. Thirty-eight craniometric measurements were taken over the models created and nine indices were calculated by using these measurements. All the characteristics examined were expressed as mean +/- SE. In the study, statistically significant differences were found between females and males in terms of greatest neurocranium breadth, facial breadth, greatest palatal breadth (p < 0.05) and height of the foramen magnum (p < 0.01) parameters. No statistically significant difference was observed between the sexes in the calculated index values (p > 0.05). In conclusion, it is thought that the findings obtained from the study will contribute to the zooarchaeology and sheep taxonomy of Mesopotamian region.
Keywords: 3D reconstruction; Hamdani sheep; morphometry; skull